Hubungan Pengetahuan, Status Gizi, dan Keterpaparan Media Massa dengan Terjadinya Menarche Dini - Epiyanti; Nur Handayani; Agnomelsya Bangaran (Politeknik Karya Husada, 2025)
Background: Early menarche is acondition where a girl experiences her first menstruation before the age of 12. the age of menarche is a determinant of awoman’s physiological development which is used as a key global health indicator. Objective: To determine the relationship between knowledge, nutritional status, exposure to mass media and the occurrence of early menarche in grades V and VI at MIN 2 Bogor. Methods: This type of research is quantitative research. The desaign used in this study is descriptive analytic with a cross-sectional approach. The population in this study were all early adolescent students at MIN 2 Bogor in grades V and VI, totaling 104 students, with a sample of 35 respondents. The sampling technique used was total sampling. This study began in August 2005. The data collection tool used in this study was a questionnaire. Result: Unuvariate analysis obtained that 21 (60%) respondents experienced early menarche, 16(45,7%) respondents had good knowledge, 12 (34,3%) respondents had normal nutrition, and 14 (40,0%) respondents had been exposed to mass media. Bivariate analysis obtained a relationship between knowledge (p-Value =0.005 and oods ratio 11.733), nutritional status (p- Value= 0.001 and odds ratio = 23.750), and exposure to mass media (p- Value = 0.029 and odds ratio = 8.000) to the occurrence of early menarche in early adolescents at MIN 2 Bogor in 2025. Conclusion and Suggestions: There is a relationship between knowledge, nutritional status, exposure to mass media with the occurrence of earlymenarche in early adolescents at MIN 2 Bogor 2025. From the results of the study, it is necessary to increase insight through educational activities, both in the from of counseling on nutrion, as well as providing reproductive health education to earlyadolescents.